2014
DOI: 10.3233/rnn-140393
|View full text |Cite
|
Sign up to set email alerts
|

The effect of single session bi-cephalic transcranial direct current stimulation on gait performance in sub-acute stroke: A pilot study

Abstract: Purpose: Non-invasive brain stimulation with transcranial direct current stimulation (tDCS) modulates cortical excitability and improves upper limb motor performance when applied to chronic stroke patients. The objective was to evaluate whether tDCS can influence gait function in sub-acute stroke patients. Methods:We assessed the effect of single session, bi-cephalic tDCS on gait performance in 14 subacute patients with stroke involving the cerebral hemisphere (2-8 weeks post-stroke) in a double-blinded, sham-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 28 publications
4
58
1
1
Order By: Relevance
“…According to Grecco et al 18 ) , the effects of tDCS depend on the location and polarity of the electrodes, and the intensity of the current used to enhance the excitability of the primary motor cortex. In a pilot study, Tahtis et al 19 ) found improvements in the dynamic balance of sub-acute stroke survivors following a single session of bi-cephalic tDCS with the anodal electrode placed on the scalp over the ispilateral lower limb motor cortex and the cathode placed over the contralateral lower limb motor cortex. Duarte et al 20 ) performed anodal tDCS on children with cerebral palsy (1 mA) in five weekly sessions and found that stimulation potentiated treadmill training, with improvements in both dynamic and static balance in comparison to a group submitted to placebo tDCS.…”
Section: Discussionmentioning
confidence: 99%
“…According to Grecco et al 18 ) , the effects of tDCS depend on the location and polarity of the electrodes, and the intensity of the current used to enhance the excitability of the primary motor cortex. In a pilot study, Tahtis et al 19 ) found improvements in the dynamic balance of sub-acute stroke survivors following a single session of bi-cephalic tDCS with the anodal electrode placed on the scalp over the ispilateral lower limb motor cortex and the cathode placed over the contralateral lower limb motor cortex. Duarte et al 20 ) performed anodal tDCS on children with cerebral palsy (1 mA) in five weekly sessions and found that stimulation potentiated treadmill training, with improvements in both dynamic and static balance in comparison to a group submitted to placebo tDCS.…”
Section: Discussionmentioning
confidence: 99%
“…Cathodal tDCS significantly attenuates epileptic discharge frequency in patients ( Auvichayapat et al, 2013 ), with similar anticonvulsive properties also being observed in rats following cathodal tDCS ( Liebetanz et al, 2006b ). Finally, tDCS applied to stroke patients improves gait performance ( Tahtis et al, 2014 ), hand dexterity, and selective attention ( Au-Yeung et al, 2014 ), whereas motor and cognitive improvements were also seen in animal models of stroke ( Kim et al, 2010 ).…”
Section: The Basics Of Tdcsmentioning
confidence: 99%
“…Although the required number and maximum sessions have not been established, we prefer to follow the model used in previous studies, which for most cases had consecutive sessions of tDCS applied for 10 days, and was able to improve motor function in different phases of stroke [ 24 , 85 , 86 ].…”
Section: Interventionmentioning
confidence: 99%
“…Studies show that CIMT is associated with functional improvement in acute and subacute stages of stroke [ 20 23 ]. Although most studies in neurostimulation therapy involve post-stroke patient monitoring for short periods [ 24 , 25 ], longitudinal studies would clarify the action mechanisms and the effective duration of this association (tDCS plus CIMT) from the early stages of stroke.…”
Section: Introductionmentioning
confidence: 99%